Proteomic technologies and targets: an overview - Kolch, Walter (Henry Stewart Talks, 2013)
Introduction, The relationship between genome and proteome, Why should we analyse the proteome?, Challenges in proteome analysis, Dynamic range of the proteome, Complexity of the proteome, Spatiotemporal organisation, Dynamic changes in protein concentrations and modifications, Technologies for analysing the proteome, Mass spectrometry, Protein arrays, Imaging, Data analysis, The applications of clinical proteomics, Biomarkers, Systems biology approaches